Perceptions of Spiritual Dryness in Iran During the COVID-19 Pandemic - Büssing, Arndt (Journal of religion and health, 2021)
This study addresses perceptions of spiritual dryness (a specific form of spiritual struggle) during the COVID-19 pandemic among Iranian Muslims (n = 362), and how these perceptions can be predicted. Spiritual dryness was perceived often to regularly by 27% and occasionally by 35%. Regression models revealed that the best predictors of spiritual dryness (SDS-7) were usage of mood-enhancing medications, loneliness/social isolation and praying as positive predictors, and being restricted in daily life concerns as negative predictor. The pandemic challenges mental stability of people worldwide and may also challenge trust in God. Reliable and humble support of people experiencing these phases is required.